Transition metal oxide nanocatalysts for the deoxygenation of palm oil to green diesel - Guerrero-Corona, C. E.; Melo-Banda, J. A.; Lam-Maldonado, M.; Vega-Ibarra, L. A.; Diaz-Zavala, N. P.; Meraz-Melo, M. A. (Frontiers in Chemical Engineering, 2024)
The present work investigated the hydrodeoxygenation of palm oil by different nanocatalysts of oxides of transition metals, α -Fe2O3, NiO and NiFe2O4, synthesized by the method hot injection process. All nanomaterials were characterized by X-ray diffraction (DRX), Fourier transform infrared spectroscopy (FTIR) and dynamic light dispersion (DLS). The catalytic evaluation was carried out in a Parr-type reactor at 350 °C, 3.5 MPa of H2 pressure and 3 h of reaction. The liquid product obtained was analyzed by ultraviolet-visible light spectroscopy (UV-Vis) for the identification of the n-C16 generated during the reaction. The activity in the deoxygenation of fatty acids to produce n-C16 hydrocarbons has the following order α-Fe2O3 < NiFe2O4 < NiO.